The Use of Drilling Technique Integrated with Technology to Improve Students’ Vocabulary Mastery at SD Negeri 1 Sibangkaja - Anggreni, Ni Komang Ayu; Dewi, Kadek Sintya; Mahendrayana, Gede (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
Many Indonesian primary students still experience difficulties in acquiring English vocabulary due to limited practice, low motivation, and the minimal use of technology in classroom instruction. This study focuses on improving fifth-grade students’ vocabulary mastery at SD Negeri 1 Sibangkaja through the implementation of drilling techniques integrated with vocabulary videos. The objectives of the study were to enhance students’ vocabulary mastery and to explore students’ responses toward the use of technology-enhanced drilling techniques. The study employed Classroom Action Research consisting of a preliminary study and two action cycles, each involving planning, action, observation, and reflection. Data were collected through vocabulary tests, classroom observations, and interviews. The results showed a significant improvement in students’ vocabulary mastery across the research cycles, with all students achieving the minimum completion criteria in the second cycle. In addition, students expressed positive responses, increased motivation, and greater engagement in vocabulary learning. The study concludes that integrating drilling techniques with vocabulary videos is an effective and engaging approach to improving elementary students’ vocabulary mastery. Furthermore, this approach offers practical implications for English teachers in designing more engaging, student-centered, and technology-aligned vocabulary instruction, while also contributing empirical evidence to the growing body of research on technology-assisted language learning for young learners.